Intravenous immunoglobulin use in pediatric intensive care unit of a developing country - Humaira Jurair; Amber shabir; Kashif Hussain; Qalab-; Anwar- (Wolters Kluwer Medknow Publications, 2016)
Introduction: Intravenous immunoglobulin (IVIG) is pooled plasma product. Its use is progressively increasing for several clinical indications. Aim: We describe experience with IVIG use in Pediatric intensive care unit (PICU) of a developing country. Method: Retrospective database review was conducted at the PICU of Aga Khan Hospital, from January 2010 to June 2014. We report the demographic data, indications, efficacy and adverse effects related to use of IVIG. Results: A total of 56 patients received IVIG treatment. 58.9% (n = 33) patients were male. Twelve patients (21.4%) were <1 year of age, 21 (37.5 %) were between 1year to 5 years and 23 (41.1%) were between 6 to 16 years old. Three most common indications were myocarditis, septic shock and severe capillary leak syndrome. IVIG was found clinically efficacious in 42.9 % cases. Minor adverse events were noted in 8.9% patients. These included 2 episodes of fever, 2 episodes of body rashes and 1 episode of fluid responsive hypotension. Indications for IVIG use had an evidence category Ia / Ib in only 7.1%. Conclusion: Use of IVIG was found safe in our PICU setting. However most of the indications were not meeting high level of evidence.